An Implementation of A Combined DEA-PROMETHEE Method for The Hull of A Ship Application - Maduekwe, Victor Chidiebere; Oke, Sunday Ayoola (Universitas Atma Jaya Yogyakarta, 2021)
The selection of an appropriate parameter in a water absorption process experiment is an important route to reducing fabrication wastes and ensuring the optimum deployment of scarce process resources to the appropriate parameter. However, the literature is inadequate in providing an appropriate direction on selecting parameters for the hull of the ships' application due to the conflicting requirements of the interested parties. A novel method called the Data Environment Analysis (DEA) to overcome this problem. Preference Ranking Organization Method for Enrichment of Evaluations (PROMETHEE) method is deployed to establish the appropriate parameter in a water absorption process on epoxy composite. The net outranking results show that criterion B (final weight) is placed in the first position. The criterion A (initial weight), D (thickness), and C (length) are placed in the second, third, and fourth positions, respectively, while E (time) is not necessary to the achievement of the system's goals. The key novelty is the unique application of the fused DEA-PROMETHEE method to a composite using the Taguchi signal-to-noise ratio response table for the hull of a ship. The method enhances the performance of multiple inputs (parameters) and multiple outputs (responses). The results of the DEA method-PROMETHEE method established the potential of epoxy composite to be used on the ship for the hull component. This could reduce the waste generated in the system, and guided allocation of resources are made to the appropriate parameters and, consequently, enhance the shipping company's profit. Furthermore, the results could improve the shipping vessel performance and develop a sustainable practice, which will lengthen the lifespan of the shipping industry.